The experience of the internationalized criminal courts among requirements National justice and international criminal justice - Walhi, Elmokhtar (Journal of Human Sciences, 2021)
The international community has established six international criminal courts in areas that have known conflicts and armed conflicts, and this establishment was carried out either by means of a bilateral international agreement between the country concerned and the United Nations, or through international assistance. Every state in which that court is located, whether in terms of substantive law or procedural law. Although the statutes of these courts and their jurisprudence constitute important legal sources within the reach of the national judicial authorities, as well as their success in punishing some criminals even if they are heads of state, there are several obstacles that stood in the face of these courts, which made them not achieve the goals for which they were established, and to varying degrees.